Repurposing of parenterally administered active substances used to treat pain both systemically and locally. Issue 10 (October 2022) - Battaglia, Luigi S.; Dorati, Rossella; Maestrelli, Francesca; Conti, Bice; Gabriele, Mirko; Di Cesare Mannelli, Lorenzo; Selmin, Francesca; Cosco, Donato
Graphical abstract: Highlights: Micro- and nanosystems are exploited to repurpose old drugs. Successful alternative approaches are available for pain treatment. Abridged marketing authorization would shorten the path for official approval. Complex formulations require high level assessment. Abstract: Pain is a constant in our lives. The efficacy of drug therapy administered by the parenteral route is often limited either by the physicochemical characteristics of the drug itself or its adsorption–distribution–metabolism–excretion (ADME) mechanisms. One promising alternative is the design of innovative drug delivery systems that can improve the pharmacokinetics |(PK) and/or reduce the toxicity of traditionally used drugs. In this review, we discuss several products that have been approved by the main regulatory agencies (i.e., nano- and microsystems, implants, and oil-based solutions), highlighting the newest technologies that govern both locally and systemically the delivery of drugs. Finally, we also discuss the risk assessment of the scale-up process required, given the impact that this approach could have on drug manufacturing. Teaser: The management of pain by way of the parenteral route can be improved using complex drug delivery systems (e.g., micro- and nanosystems) which require high-level assessment and shorten the regulatory pathway.